Essential cinema : an introduction to film analysis - Lewis, Jon, 1955- (Boston, MA : Wadsworth, Cengage Learning, 2014)
Succinct, lively, and affordable, this text provides a clear focus on developing your skills in film analysis. Offering the most engaging instruction available, this exciting first edition is packed with illustrations from films that you will readily relate to. It features interviews with award-winning film practitioners, who offer insights into film form and style. Videos of the complete interviews are available through the eBook version as well as the text website. In addition, unique screening questions will help you apply chapter concepts to any film you watch, while the running glossary and end-of-text illustrated glossary ensure that you have easy access to full explanations of concepts.
Includes indexes.
Keywords: Film criticism; Motion pictures